Implementasi Program Wajib Pesantren dalam Pembentukan Karakter Siswa di MTs Darul Ulum Muara Kiawai Pasaman Barat - Tika Lestari; Fenny Ayu Monia (YASIN, 2026)
The implementation of the Compulsory Pesantren Program in shaping students’ character has received attention in various studies of Islamic education, but studies that specifically discuss its implementation process through the aspects of planning, implementation, and evaluation in the context of pesantren-based madrasahs remain limited. This study aims to describe the implementation of the Compulsory Pesantren Program in shaping students’ character at MTs Darul Ulum Muara Kiawai, West Pasaman. This study used a qualitative approach with a case study design. The research informants included the head of the madrasah, pesantren leaders, teachers, dormitory supervisors, students, and parents, who were selected through purposive sampling and snowball sampling techniques. Data were collected through interviews, observation, and documentation, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The results showed that the Compulsory Pesantren Program was implemented through systematic planning, continuous religious activities and character habituation, and periodic evaluation. The implementation of this program contributed to the development of students’ religious character, discipline, responsibility, independence, honesty, social care, and politeness. These findings contribute to the development of studies on pesantren-based character education and broaden understanding of the integration of formal education and pesantren education in shaping students’ character. The conclusion of this study affirms that habituation, role modeling, supervision, and continuous evaluation are important factors in supporting the success of character education in pesantren-based madrasahs. The implications of this study include theoretical contributions to the development of Islamic education literature and practical implications for madrasahs and pesantren in developing effective and sustainable character education programs.